An Exploration of the Possibilities of Current Mental Health Services to Tackle Transgenerational Effects of Parental Mental Illnesses on Offspring Adjustment in Lithuania - Lesinskiene, Sigita (Frontiers in Psychiatry, 2021)
The topic of mental health and mental disorders is very sensitive and delicate in families and the society. Stigma is one of the main reasons for little help-seeking for mental disorders. Transgenerational effects of mental disorders is the utmost sensitive theme that brings difficulties for service organization and research. By emphasizing the importance of the effects of parental mental illnesses on the health of offspring and their adjustment, together with sharing the international experience between professionals, both the administration of services and society could provide opportunities for further positive change in this little-studied but utmost actual field. There is still a lack of appropriate long term systematic programs and ways to overcome complex organizational challenges. Sharing international experience and research could help find ways that best fit the situations in each country. After a descriptive analysis of the current system of mental health services in Lithuania, opportunities were sought to meet the needs of children and adolescents whose parents have mental disorders by ensuring their healthy psychosocial development. Child and adolescent psychiatry services are a more favorable and less stigmatized area in Lithuania than adult psychiatry, so assistance and specialized programs for children of parents with mental health problems could be organized using the country's relatively well-developed network of child and adolescent psychiatric and pediatric services. For such a small country with limited resources, there could be a possibility to use and strengthen the existing network of services together with finding opportunities for mixed models of financing and cooperation with non-governmental initiatives and organizations. A unique network of primary mental health outpatient centers that provide services for adults and children/adolescents could serve as a reasonable basis for the systematic implementation of specialized programs and initiatives in this field. This network is still not adequately used in the organization of mental health prevention, early intervention, and complex treatment services for the children of parents with mental illness.